2013
DOI: 10.1606/1044-3894.4322
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Marital Status and Depressive Symptoms among Asian Americans with Same-Sex Partners

Abstract: By observing factors that predict depressive symptoms, this study examines the need to identify whether the perception or the reality of being married helps Asian Americans in same-sex partnerships improve their mental health. In a Texas sample (N = 1,840) of respondents to a survey on needs and hardships of Asian ethnic communities, 163 individuals (n = 9%) reported having a same-sex partner; this subsample reported a 24.5% depression rate as measured by the Hopkins Symptoms Checklist. Logistic regression res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…LGBTQ. In 2013, eight articles were identified in the LGBTQ topic area (n ϭ 8; e.g., Leung, Cheung, & Luu, 2013a;Leung, Cheung, & Luu, 2013b;Nadal & Corpus, 2013;Szymanski & Sung, 2013). Compared with last year's review with no articles related to LGBTQ issues, there was an increase of studies published in 2013.…”
Section: Resultsmentioning
confidence: 99%
“…LGBTQ. In 2013, eight articles were identified in the LGBTQ topic area (n ϭ 8; e.g., Leung, Cheung, & Luu, 2013a;Leung, Cheung, & Luu, 2013b;Nadal & Corpus, 2013;Szymanski & Sung, 2013). Compared with last year's review with no articles related to LGBTQ issues, there was an increase of studies published in 2013.…”
Section: Resultsmentioning
confidence: 99%
“…A cutoff score of 1.75 is used to identify clinically significant symptoms for each subscale (Sandanger et al., 1999). Evidence of validity was demonstrated by correlations of the HSCL-25 with medical doctor’s global assessment of psychological distress and other measures of emotional symptoms (Hesbacher, Rickels, Morris, Newman, & Rosenfeld, 1980), and it has been used in a sample of same-sex couples (Leung, Cheung, & Lu, 2013). The internal validity of the measure in the current sample was good (α = .93).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found high rates of depression in LGBTQ Asian Americans. Studies have varied in their estimates, with point prevalence rates as high as 16% and lifetime prevalence rates as high as 97% (Choi & Coates, 1993;Leung, Cheung, & Luu, 2013).…”
Section: Depression Self-harm and Suicidalitymentioning
confidence: 99%